Group affiliation and earnings management of Asian IPO issuers - Roy Kouwenberg (2018)
© 2015, Springer Science+Business Media New York. We study how group affiliation, a firm being a member of a business group, affects earnings management around initial public offerings (IPOs) in nine Asian countries. Our empirical evidence shows that Asian IPO issuers tend to manage earnings more aggressively than matching non-IPO firms from the same industry: discretionary accruals are higher by 3 % of total assets. Earnings management is especially pronounced among the quartile of IPO firms with the highest dependence on external capital. However, group-affiliated issuers have substantially lower levels of earnings management compared to non-group issuers (discretionary accruals are lower by 6.8 % of total assets), even when their dependence on external capital is high. Our results suggest that group-affiliated IPO issuers in Asia can raise funds more easily than non-group issuers, and as a result they have a lower need to manipulate earnings. We also find a negative relation between underwriter reputation and earnings management, which suggests that reputable underwriters help certify the validity of information disclosure for IPOs.